Pengaruh Pengetahuan Dan Lingkungan Wajib Pajak Terhadap Kepatuhan Wajib Pajak Melalui Kesadaran Sebagai Variabel Intervening - Gessy Ghesiyah (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Kristen Indonesia Paulus, 2022)
Abstract. This study aims to determine whether knowledge of taxation and the taxpayer environment has an effect on taxpayer compliance through taxpayer awareness as an intervening variable. The population in this study is the Marketplace registered in the membership directory of the Indonesian E-Commerce Association (idEA). The results of partial hypothesis testing indicate that knowledge of taxation and the taxpayer's environment has a significant effect on taxpayer awareness. The results of partial hypothesis testing indicate that knowledge of taxation and the taxpayer's environment has a significant effect on taxpayer compliance. The results of simultaneous hypothesis testing show that Tax Knowledge Indirect Positive Effect on Taxpayer Compliance with Taxpayer Awareness as an Intervening Variable while the Taxpayer's Environment has No Indirect Positive Effect on Taxpayer Compliance with Taxpayer Awareness as an Intervening Variable.